Brain natriuretic peptide and atrial septal defect size in children - Siti Aizah Lawang; Haryanty Kartini Huntoyungo; Dasril Daud (Indonesian Pediatric Society, 2020)
Background Atrial septal defect (ASD) is one of the most common forms of congenital heart disease (CHD). Brain natriuretic peptide (BNP) is a heart marker released into the circulation during pressure overload, heart volume expansion, and increased stress on +the myocardial wall. Objective To assess for a possible association between atrial septal defect size and BNP level in pediatric patients. Methods This cross sectional study on children with ASD was done from March to December 2018 in pediatric outpatients and inpatients at Dr. Wahidin Sudirohusodo Hospital, Makassar, South Sulawesi. Measurement of ASD defect was conducted using echocardiography and categorized as small defect (<3 mm), medium defect (3-8 mm), and large defect (>8 mm). Brain natriuretic peptide was measured using radioimmunoassay and immunoradiometricassay. Nutritional status was categorized using WHO if the patients aged younger than 5 years and NCHS for patients aged equal or more than 5-year-old. Results Mean BNP levels were 65.5 pg/mL in the small ASD group, 273.2 pg/mL in the moderate ASD group, and in 654.5 pg/mL in the large ASD group, with significant differences among ASD groups. We found a significant positive correlation between BNP levels and ASD diameter (r=0.829; P=0.001), with Y regression equation of: (BNP level) =2.624 + 0.009X (ASD diameter in mm). Conclusion Brain natriuretic peptide levels have significant positive correlation with ASD size. Hence, BNP measurements can be used to predict septal defect size in children with ASD. Acyanotic CHD patients with suspected ASD and high BNP levels may have moderate-to-large ASDs.